Determining Factors for the Success of Digital Financial Inclusion in Industrial Estates in Indonesia - Amalia, Mekar Meilisa (Westscience Press, 2025)
This study explores the determining factors for the success of digital financial inclusion in industrial estates in Indonesia, focusing on technological infrastructure, regulatory environment, financial literacy, and socio-economic characteristics. A quantitative approach was employed, using a sample of 86 respondents from various industrial estates across Indonesia. Data were collected through a structured survey with a Likert scale (1-5) and analyzed using SPSS version 25. The findings reveal that technological infrastructure, regulatory environment, and financial literacy are the strongest predictors of the success of digital financial inclusion, with socio-economic characteristics also playing a significant, though weaker, role. The regression model explained 69% of the variance in the success of digital financial inclusion. The study emphasizes the need for improved infrastructure, supportive government policies, and financial literacy programs to enhance the adoption and effectiveness of digital financial services. These findings provide valuable insights for policymakers, financial institutions, and business leaders seeking to foster greater financial inclusion in industrial estates.